Meningkatkan Adaptasi Anak Belajar dalam Situasi yang Berubah Bermakna di Sekolah Inklusi Sentra Salsabila - Taufiq Fredrik Pasiak; Nurfitri Bustamam; Muhammad Reiza; Erna Harfiani; Retno Yulianti; Widianingsih Widianingsih; Manpan Drajat (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Sekolah Inklusi Sentra Salsabila provides curriculum and infrastructure to support children with special needs and normal children receiving education together. The COVID-19 pandemic impacts students’ lives, students can experience nutritional problems due to family economic crises and learning problems due to activities restriction outside the home. Situations that have changed significantly during the pandemic can cause stress and health problems in children. Community service activities (CSA) are carried out so that the school knows the health status of students and parents of students have sufficient knowledge as a first step to make efforts to improve students' adaptation to learning. Parents of students are given counseling about adolescent mental health, balanced nutrition, and worm infections. Students’ body composition was measured using Tanita MC-980 MA, then stress and resilience levels were measured using Heart Rate Variability Analyzer-Medicore SA 3000P. The results of the CSA show that parents of students already have sufficient knowledge, and it is known that some students need intervention related to their physical and mental health status. It can be concluded that this CSA succeeded in helping schools and parents to plan intervention steps to improve students’ adaptation to learning.